Clinical Case 15—Warburg effect and pulmonary embolism: a confounding clinical case. (21st October 2022) - Ferreira, Gonçalo Rafael Marques; Correia, Joana; Fiuza, João; Santos, João Miguel; Neto, Vanda; Cunha, Joana; Fernandes, Filipe; Pires, Inês; Marmelo, Bruno; Cabral, Costa
Abstract: Presentation: A 61 year old man with a history of multiple lymph node metastasis of unknown primary cancer was admitted in the Emergency Room with sudden dyspnea preceded by left leg swelling. Physical examination revealed a blood pressure of 91/70mmHg, tachycardia, tachypnea and signs of deep vein thrombosis (DVT). Diagnosis and management: Blood analysis showed increased serum lactate (SL) (5, 5 mmol/L), a slight increase of cardiac enzymes and hypoglycemia, and imagiologic tests showed signs of bilateral pulmonary embolism (PE) and an increase of the right cardiac chambers. The patient was hospitalized with the diagnosis of intermediate-high risk PE. Because the patient presented persistent elevated SL and borderline hypotension, fibrinolysis was performed. However, the patient maintained high SL levels and hypotensive profile. After receiving the lymph node's biopsy result, which pointed towards a follicular lymphoma, the persistent hyperlactatemia, together with the hypoglycemic profile, was interpreted as a consequence of the Warburg Effect. Luckily, the patient didn't had any side effects of the fibrinolytic treatment. Learning points: Acute high risk PE is marked by the presence of haemodynamic instability at presentation, and the finding of increased SL suggests peripheral hypoperfusion. Systemic thrombolytic therapy is indicated in most of patients with high risk PE. However, there are other causes of hyperlactatemia which the physician must be aware, as it can act as a confounder of PE risk assessment. The Warburg Effect may cause elevated SL in patients with cancer, which in turn are at risk of developing PE.